PENGARUH PENGGUNAAN AGREGAT HALUS JAMUR UJUNG PADA CAMPURAN LASTON AC-WC - Ardian Fahmi; Sofyan M. Saleh; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The good quality of road surface layers are strongly influenced by the materials used such as the aggregate composition, asphalt, and filler. Fine Aggregate from Jamur Ujung is a local aggregate that can be found in  Bener Meriah District. It has not been utilized maximally  due to its porosity and high aggregate absorption. This research is conducted to see improvement of the characteristics that can be done to the asphalt mixture using the fine aggregate from Jamur Ujung. It is expected that this aggregate is feasible to be used as an asphalt mixture material in accordance to the specifications set by Bina Marga. This research was conducted by producing test objects (specimen) to determine the optimum asphalt content using standard aggregate from Lepung Baleuh, Kuta Cot Glie, Aceh Besar District, then the test object with combination of standard fine aggregate mixture with fine aggregate of Jamur Ujung with the variation percentage respectively by 25%, 50%, 75% and 100% at 5.35%, 5.87% and 6.35% asphalt content in the mixture of AC-WC. The results of this study show the mixture that meets specifications that represent all Marshall characteristics is a mixture with substitution of 50% fine aggregate of Jamur Ujung at 5.87% asphalt content with a stability value of 1355.90 Kg. Results of this research also show that fine aggregate of Jamur Ujung can be used as road construction project especially for asphalt concrete work (AC-WC).